Application Of The Number Head Together Using Print Digital Puzzle - Eny Suryaningsih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study aims to determine the increase in learning outcomes of the basic material anatomy structure of animal cells and plant cells in 11th grade students of MIA1 SMAN 25 Tangerang Regency with the application of the Numbered Head Together (N.H.T) learning model using puzzle media. The type of research used is classroom action research with two cycles, each cycle includes stages of planning, implementation, observation/evaluation and reflection. The research subjects were 36 people. Data collection using a test instrument. Data analysis is descriptive qualitative. It is known that the average learning outcome in the pre-cycle is 55. The results of data analysis in the first cycle, the average learning outcome reaches 68, continued in the second cycle, the average learning outcome increases by 76. The conclusion of this study shows that the application of the N.H.T learning model using puzzle digital print can improve learning outcomes of cell structure.